The role of organizational context in fostering employee proactive behavior: The interplay between HR system configurations and relational climates. Issue 5 (October 2016) - Batistič, Saša; Černe, Matej; Kaše, Robert; Zupic, Ivan
Abstract: Emphasizing the role of the organizational context and adopting a multilevel approach, we propose that the interplay between HR system configurations and relational climates has a cross-level effect on employee proactive behavior. Using a sample of 211 employees in 25 companies, we show that the laissez-faire context – featuring a combination of a weak compliance HR configuration and a strong market-pricing relational climate – is better suited for fostering employee proactive behavior than the nurturing context, which is characterized by a strong HR commitment configuration and a strong communal-sharing relational climate. We also found that combining a strong HR commitment configuration with a weak communal-sharing climate is associated with more employee proactivity. We discuss what our findings suggest about the interaction between HR system configurations and organizational climate dimensions and about their role in influencing individual-level outcomes.